(untitled) (The International Journal of Educational Sciences and Arts, 2023)
If historical interpretation is an intellectual process whose goal is to seek to understand the truth of historical events and phenomena through analyzing the temporal, cultural, and social context in which they occurred, then to better understand the past it is necessary to uncover the driving forces that were behind the events based on the study of historical sources, and to reveal the factors that These events influenced and affected the social, economic, cultural and political conditions that shaped the lives of people and groups in the past. If we take into account that the process of history - as some believe - requires only experienced specialists, can there be room for others to express their opinions in the service of historical issues? From here we may ask the following questions: Definition of historian? Introduce the first basic sources of history, represented by the written source and document, and the second linked to the results of archaeological research, how can poetry and its interpretation serve a historical issue? Taking into account these starting points, we will try, through the example of Mahmoud Shukri Al-Alusi and his book Attaining Knowledge in Knowing the Conditions of the Arabs, to answer our questions.